TINJAUAN PUTUSAN HAKIM TENTANG PELAKSANAAN EKSEKUSI TERHADAP NO. 1099/PID.B/2017/PN.SBY - IAN SOEMARDI; ARIEF DWI ATMOKO (Fakultas Hukum Universitas Narotama, 2020)
The purpose of this study is to examine and analyze the decision of the Surabaya district court and follow-up on these decisions in the criminal justice system in Indonesia, as we know that criminal law enforcement includes a series of processes starting from investigation, investigation, prosecution and will lead to the formation of a judge's decision. as the peak and basis for the execution of the convicted person. Judges in drafting their decisions must reflect a sense of justice, a sense of usefulness and legal certainty. in the decision against decision no. 1099 / PID.B / 2017 / PN.SBY, which the author reviewed and analyzed, that the judge in compiling his decision did not include the defendant to leave the house at issue in court so that in the provisions of Article 167 Paragraph (1) of the Criminal Procedure Code so that the decision does not reflect justice , benefits and legal certainty in Indonesia.Keywords: verdict, fairness, benefit, certainty